Tackling trypanosomiasis - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Despite many years of baffle, the number one' problem facing livestock in Africa is still the indomitable tsetse fly. The limitations on raising livestock imposed by the typanosomiasis that it spreads pose increasing problems for African countries...